Analisis Kelayakan Usaha Perikanan Tangkap Menggunakan Alat Tangkap Modern dan Tradisional di Kota Bengkulu - Andreas Jorghy Parapat; Indra Cahyadinata; Gita Mulyasari; Daniel Surya Parapat; Karina Silaen (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Small-scale fishing businesses face challenges in maintaining financial viability due to fluctuations in catches, changes in operational costs, and uncertainty in fishermen's income. These conditions require a business feasibility analysis to support decision-making and the sustainability of capture fisheries businesses. This study aims to analyze the financial feasibility and sensitivity level of fishing businesses using drift gillnets and boat lift nets in Bengkulu City. The study used a quantitative approach with a case study method in two locations, namely Baai Island and the Kota Tuo area, Bengkulu. Primary data was obtained through a survey of fishing vessel owners and analyzed using indicators such as Benefit-Cost Ratio (B/C Ratio), Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and sensitivity analysis. The results of the study indicate that both types of businesses are feasible based on all financial feasibility indicators. The sensitivity analysis shows that the drift gillnet business becomes unfeasible if revenue decreases by 80%, while the boat lift net business becomes unfeasible if operational costs increase by 22%. Comparatively, the drift gillnet business has a better level of financial viability than the boat lift net business. This finding indicates that while both businesses are feasible to develop, the drift gillnet business has greater financial resilience to changing economic conditions, making it a potentially more sustainable alternative for fishermen in Bengkulu City.